RANCANGAN BOOKLET BIOLOGI SMA KELAS X PADA MATERI BAKTERI - Siagian, Lili Rahma; Sayuti, Irda; Mahadi, Imam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the potential of the Booklet design in high school learning on bacterial material for class X. This research was conducted at the Binawidya Campus, Riau University in December 2020 - January 2021. This study was carried out with the ADDIE design, namely the analysis and design stages. Booklet design in the form of an analysis of the potential development of learning media for high school bacteria material class X Semester I. The research uses an experimental method with a quantitative descriptive type of research. Based on the potential analysis, it was found that the bacteria Bacillus cereus strain IMB-11 has the ability to biodegrader against used lubricating oil, which can be used as a booklet design for class X bacteria in SMA KD 3.5 and KD 4.5.Key Words: Booklet, Bacteria Material.